Pengaruh Model Pembelajaran Contextual Teaching And Learning(CTL) Terhadap Hasil Belajar Siswa Pada Subtema 1 Keberagaman Budaya Bangsaku Kelas IV SD Negeri 122398 Pematang Siantar - Pransiska Agustina Pasaribu (CV. KAMPUS AKADEMIK PUBLISING, 2023)
One of the most important things in determining the progress and development of a nation is education. Where education will form quality human resources capable of following the current of increasingly advanced developments. This research aims to determine whether there is an influence of the Contextual Teaching and Learning (CTL) Learning Model on student learning outcomes in the Theme of the Beauty of Togetherness, Subtheme 1, Cultural Diversity of My Nation, class IV at SD Negeri 122398 Pematang Siantar in the 2023/2024 Academic Year. Based on the hypothesis test (t test) it can be concluded that the use of the Contextual Teaching and Learning (CTL) learning model has an effect on student learning outcomes after it is known that the t value is 13.20 with a frequency (dk) of 25-1 = 24. At the significant level α = 0.005 then we get ttable = 2.064. So we get tcount > ttable 13.20 > 2.064. So it can be concluded that H0 is rejected and Ha is accepted. So there is an influence of the Contextual Teaching and Learning (CTL) Learning Model on the learning outcomes of class IV students in Theme 1 The Beauty of Togetherness with sub-theme 1 Cultural Diversity of My Nation at SDN 122398 Pematang Siantar.